Interstitial HDR brachytherapy (HDR-BT) in early stage mobile tongue cancers in young patients – Gliwice experience - Kellas-Ślęczka, Sylwia (J Contemp Brachytherapy, 2010)
PURPOSE: In early stage mobile tongue cancer radical radiotherapy offers good local control and organ preservation, which is especially important in the group of young patients. In our department, for many years HDR-BT has been performed in mobile tongue cancers as a sole treatment or as a “boost” with EBRT. The aim of the study was to show our experience with HDR-BT in early stage mobile tongue cancers among young patients. MATERIAL AND METHODS: From 2001 to 2006 in Maria Skłodowska-Curie Memorial Cancer Centre and Institute of Oncology, Gliwice Branch, five patients under 45 years with mobile tongue cancer were treated with HDR brachytherapy (T1N0M0 – 3/5 and T2N0M0 – 2/5); 4 with HDR brachytherapy “boost” and 1 as a sole treatment. One woman was previously treated with tumour resection, but because of positive surgical margins was referred for radiotherapy. All patients had clinically negative lymph nodes, without dissection. They were treated with interstitial HDR-BT (3-8 catheters). In 4 patients treated with HDR-BT as a “boost”, total doses ranged from 18 to 21 Gy given in 6-7 fractions (twice a day, 3 Gy per fraction). Total doses in EBRT (to local lymph nodes and tumour bed) ranged from 50 to 60 Gy (1.8-2 Gy per fraction 5 days/week). One patient, treated with radical HDR brachytherapy, received 45 Gy in 10 fractions and 50 Gy in EBRT to regional lymph nodes. RESULTS: We did not notice local recurrences or distant metastases in our group of patients. Median follow-up was 67 months (range 47-79 months). All patients preserved normal tongue function. A severe late complication occurred in 1 patient – fracture of the mandible. CONCLUSIONS: In the analysed group of young patients with mobile tongue cancer interstitial HDR brachytherapy in combination with EBRT was an effective and well tolerated treatment modality which allowed preservation of the tongue and its function.